5x+40f(x)x=-5

Simple and best practice solution for 5x+40f(x)x=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+40f(x)x=-5 equation:


Simplifying
5x + 40f(x) * x = -5

Multiply f * x
5x + 40fx * x = -5

Multiply fx * x
5x + 40fx2 = -5

Reorder the terms:
40fx2 + 5x = -5

Solving
40fx2 + 5x = -5

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5x' to each side of the equation.
40fx2 + 5x + -5x = -5 + -5x

Combine like terms: 5x + -5x = 0
40fx2 + 0 = -5 + -5x
40fx2 = -5 + -5x

Divide each side by '40x2'.
f = -0.125x-2 + -0.125x-1

Simplifying
f = -0.125x-2 + -0.125x-1

See similar equations:

| 6x^2=12x-9 | | Cos(4x-10)=0 | | 7x-5y=-68 | | H=-5t^2+7t-4 | | 1x+4y=120 | | 1x+4y=11120 | | 2-2v=v+64 | | x-11=90 | | 3x+y-z=1 | | 0.9375=x+0.25(3) | | 6x-2y-z=-14 | | f(x)=13x+52 | | 2lgx=2 | | (n+5)(p-14)=1400 | | 6y+2z=a+3y | | 2x+3y+z=1 | | 6y+2z=a+3fory | | 0=-5x^3+25x^3-17x | | 4x+3y=330 | | 10-5x=3x+6 | | -3(4p+4)-2(6-11p)=3(8+3p) | | 29+0.25p=59 | | 0.3x+0.4=0.28x+1.16 | | lny=7 | | 0.011x^3+22x-203=0 | | 14=2.50+2.30(m-1) | | E=f-g | | 2=18*3g | | 2(1-3x)=12 | | 3x+30+2x=360 | | 4x-1=-61 | | 108=-5(x-8)-(x+3) |

Equations solver categories